Distributed Risk... Lottery-like Bets in Politics as a Response to Constitutional Changes - Sergio David Valenzuela; Marcos Walter Medina (European Scientific Journal, ESJ, 2017)
The paper aims to analyze the simultaneous candidatures used in municipal elections in the province of Chaco in 1995, as responses to changes in electoral systems. The analysis is centered on the candidates who ran concurrently to two positions – mayor and councilor - at the same level of government in the same election; Discriminating winners from losers. It can be stated that the term quinieleras candidacies, resulted in a strategy that, out of a total of forty candidates, served to win to the head (mayor) three candidates of the Provincial party Acción Chaqueña; And in the prizes was effective for 11 candidates, of which nine correspond to Acción Chaqueña and two to the Radical Civic Union, political party of national order. The conclusions that the work leaves could be used for the analysis of the internal rules of the political parties, and to propose norms that really regulate the operation of the political parties.